Metode Pembelajaran Partisipatif dalam Membentuk Disiplin Belajar dan Implikasinya terhadap Hasil Pendidikan Agama Islam - Didit Darmawan; Salsabila Putri (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This literature study aims to analyze the influence of participatory learning methods on the formation of learning discipline and its impact on learning outcomes in Islamic Religious Education. Using a qualitative library research approach, this study synthesizes concepts from various relevant theoretical sources. The findings indicate that participatory learning methods positively influence the formation of student learning discipline through active involvement, sense of ownership, social responsibility, learning from natural consequences, and fulfillment of basic psychological needs. The discipline formed through this process is internal, stable, and sustainable because it arises from self-awareness, not external pressure. Learning discipline significantly impacts PAI learning outcomes in the cognitive domain through regular repetition and deep processing, in the affective domain through gradual value internalization, and in the psychomotor domain through continuous practice. Learning discipline also increases self-efficacy, reduces evaluation stress, and optimizes the use of learning resources. This study implies the need for a paradigm shift in PAI learning towards participatory student-centered approaches and the creation of school environments that support the growth of internal discipline through real responsibility and natural consequences.